Glycogen Synthase Kinase-3 Inhibitors: Preclinical and Clinical Focus on CNS-A Decade Onward - Arciniegas Ruiz, Sara Melisa; Eldar-Finkelman, Hagit (Frontiers in Molecular Neuroscience, 2022)
The protein kinase, GSK-3, participates in diverse biological processes and is now recognized a promising drug discovery target in treating multiple pathological conditions. Over the last decade, a range of newly developed GSK-3 inhibitors of diverse chemotypes and inhibition modes has been developed. Even more conspicuous is the dramatic increase in the indications that were tested from mood and behavior disorders, autism and cognitive disabilities, to neurodegeneration, brain injury and pain. Indeed, clinical and pre-clinical studies were largely expanded uncovering new mechanisms and novel insights into the contribution of GSK-3 to neurodegeneration and CNS-related disorders. In this review we summarize new developments in the field and describe the use of GSK-3 inhibitors in the variety of CNS disorders. This remarkable volume of information being generated undoubtedly reflects the great interest, as well as the intense hope, in developing potent and safe GSK-3 inhibitors in clinical practice.